Survey on patient’s satisfaction on the service quality in an emergency department in Malaysia - Basauhra Singh, Harvinderjit Kaur; Subramanian, Pathmawathi; Chong, Mei Chan; Jamaludin, Sumaiyah @ ThandarSoe (Research & review, 2016)
Patients' experience in the emergency department in terms of service, communication, waiting time, competence and facility are important indicators in improving quality care. The aim of this study was to explore patient’s satisfaction level on care of five domains; services, communication, waiting time, competence and facility in the emergency department. A cross-sectional study design using PEQ (Patient Experience Questionnaire). Convenience sampling method used requiring participants to complete the questionnaire prior to discharge. Data was analysed with SPSS version 20. Descriptive and Pearson Chi Square was used to determine the association.324 questionnaires returned. Descriptive analysis showed 67.9% were not satisfied with their experiences. The mean service scored 65.90 ± 31.91, communication scored 65.00 ± 35.76, facility scored 63.33 ± 34.53, competence scored 54.89 ± 35.18 and waiting time scored 49.77 ± 32.65. Service has significance association with education and age group. This study has showed the importance of communication skill and a well-organized emergency department right from the triage till discharge to improve the satisfaction level of patients. Hence the department should recognize these needs and increase the provision of training need for staff in order in contribution to improve the communication skill of the healthcare provider.